PENGARUH KEGIATAN SOSIALISASI KPU TERHADAP SIKAP MAHASISWA PADA KEGIATAN PEMILU - Muhammad Tanziil Suherman; M Rijal Amirulloh (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2018)
ABSTRACT The research is entitled “The Influence of General Election Commision toward Student Attitude on Election Activity”. Research method applies quantitative with path analysis. Research aims to know how big the influence of socialization activity source factor toward student attitude on election activity, to know how big the influence of message factor, and to know how big the influence of subject receiver factor toward student attitude on election activity. The result research shows that each variable has sifnificant influence toward student attitude on election activity. Source factor variable has significant influence toward student attitude as much as 78,9 %, socialization message factor variable has significant influence toward student attitude as much as 85,5%, subject receiver factor has sifnificant influence toward student attitude as much as 81,1%. Message variable becomes the most influence variable toward student attitude on election activity. It can be concluded that message factor variable has the most influence factor compares to other factor. Sending factual message based on fact, sending a trending topic message, and such message is thought to be important so that message can change someone attitude toward something. Besides, source factor has an influence. Cridible factor and expert can make communicant believe and enable to be persuaded well especially previous attitude will be able to convinced to change.